PEMETAAN LOKASI KULINER BERBASIS METODE SPHERICAL COSINE PADA KOTA GORONTALO - F, Farid (Program Vokasi Universitas Negeri Gorontalo, 2025)
The culinary industry in Gorontalo City has grown rapidly along with tourism activities and urban expansion. However, spatial data regarding the distribution and accessibility of culinary locations remain limited. This study aims to design a desktop-based Geographic Information System (GIS) for mapping culinary locations using the Spherical Cosine method. This method accurately calculates distances between geographic coordinates (latitude and longitude) on the Earth’s surface. Spatial data were obtained from administrative maps of Gorontalo City, and attribute data were collected through field surveys. The result is a GIS application that displays culinary spots—restaurants, cafes, and street food vendors—on an interactive digital map. The system calculates distances between locations and provides detailed facility information. This platform allows users to find nearby food places easily, while local governments can utilize it for planning culinary tourism and local economic development.